Decision Support System in Employee Admissions Using Simple Additive Weighting Algorithm in CV.Source of Shared Solutions - Syahrul Rofiq Abdillah Fadli; Dwi Hartanti; Agustina Srirahayu (Publikasi Indonesia, 2024)
CV. Sumber Solusi Bersama, a software house company in Sukoharjo, faces challenges in the employee recruitment process that is still done manually. This research aims to develop a decision support system (SPK) for employee admission using the Simple Additive Weighting (SAW) algorithm. The SAW algorithm was chosen because of its ability to analyze and give weight to each criterion for the best decision-making. This research uses the waterfall system development method which is part of the System Development Life Cycle (SDLC). This system is expected to increase efficiency and accuracy in the employee selection process, as well as support fairer and more appropriate decision-making. Software feasibility testing conducted by CV. Implementation of SPK with SAW algorithm in CV. Sumber Solusi Bersama provides an alternative way to select employees that is more systematic and structured, so that it can help in achieving the company's strategic goals.